Sprachliche Persuasionsmittel der rechtspopulistischen Propaganda gestern und heute - Gannuscio, Vincenzo (Linguistik Online, 2019)
Persuasion is the central element of political propaganda of all times. From a historical point of view, it is a fact that, especially in conflict situations, the hegemonic actors adopt specific techniques and language choices for purposes of propaganda. The question of interest is in what ways and to what extent they are used in a targeted manner in order to influence different types of low- and middle-class audiences. A well-documented example is the persuasive use of language in Nazi propaganda before and during World War II. In this context, our question is whether past and present-day propagandistic and electoral campaigns make recourse to the same linguistic devices and strategies in order to persuade their intended audience. To this purpose, we shall concentrate on Hitler’s propaganda by primarily drawing on Victor Klemperer's (1933–1945) diaries and compare his linguistic observations to a corpus of campaigning speeches and programs by the German right-wing populist party AfD (Alternative für Deutschland).